Sosialisasi dengan Tema Memahami Hukum Perjanjian dan Dampak Psikologisnya dalam Kehidupan di Era Globalisasi di Masyarakat Sukamarga: Pengabdian - Mohammad Hifni; Novita Sari; Tiara Kurniati; Muhammad Adnan Faidh; Adnin Chiesa Syahwanes; Siti Rohayati; Ajeng Trihartini; Muhammad Idham Alfaridi; Dewi Lestari Pratami; Mutia Nandika Sukma (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
A socialization activity with the theme "Understanding Contract Law and Its Psychological Impact on Life in the Era of Globalization" was held in Sukamarga Village as a form of community service by postgraduate students. This activity was motivated by the low level of legal literacy in the community in understanding legally valid agreements, as well as a lack of awareness of the psychological impact that can arise from legal conflicts, especially in the context of globalization which presents various forms of cooperation and transactions, both in person and digitally. The purpose of this activity was to increase public understanding of the elements of contract law and to identify potential mental stress arising from legal issues, such as stress, anxiety, and interpersonal conflict. The implementation method of this activity included material presentation, interactive discussions, and simple case studies to connect theory with real conditions experienced by the community. The results of the activity showed the enthusiasm of participants in absorbing the material and sharing experiences related to legal issues they experienced. Participants recognized the importance of understanding the contents of the agreement before agreeing to an agreement and the importance of maintaining mental health in responding to legal conflicts. The conclusion of this activity is that legal understanding and a psychological approach provided simultaneously can increase public awareness and resilience in facing the challenges of life in the era of globalization, while simultaneously forming a legally intelligent and mentally healthy society.